Dichloromethane as an economic alternative to chloroform in the extraction of DNA from plant tissues - Chavez, Alba L.; Vergara, CE; Mayer, Jorge Edgard (1995)
Processing of large numbers smaples of plant tissue samples for molecular mapping and gene tagging requires methods that are quick, simple, and cheap, and that eventually can be automated. Organic solvents used for DNA extraction can represent a significant proportion of the overall cost. In this study we examined dichloromethane as a replacement for chloroform to be used in combination with phenol.